PENGARUH KUALITAS LAYANAN, KOMPETENSI TENAGA PENJUALAN, PERSEPSI HARGA, DAN VARIASI PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI ( Studi Empiris Pada PT. Libera Farma Semarang) (Proceeding Fakultas Ekonomi, 2014)
This study aims to examine and analyze whether there is the influence service quality, sales forcecompetence, perceptions of price, and variety of products to the customer satisfaction. The influenceservice quality and sales force competence to the customer loyality. The influence customer satisfactionwhich can mediate customer loyalty. Planning of this research used explanatory research to know therelationship between variable. The respondents of this research are 100 pharmacies in the Semarang City used probability sampling technique which is used simple random sampling. From the result analysis to the research model which have been examined, it is indicated that service quality, sales force competence, perception of price, and variety products are influenced positive and significant to the customer satisfaction. The result of mediation is also indicated that customer satisfaction does mediate the servicequality, sales force competence, perception of price and product variety.Keywords: service quality, sales force competence, perception of price, customer satisfaction, and